Seamless Video Session Handoff between WLANs. (9th February 2010) - Monteiro, Claudio de Castro; Gondim, Paulo Roberto de Lira; Rios, Vinícius de Miranda
Abstract : Handoff in a distributed IEEE 802.11 Wireless LAN network is a source of significant amount of problems on the video transmission environment. The visual quality of video streaming applications is lowered when stations are in handoff status. In this paper, we introduce an architecture of a session proxy (SP), which tries to preserve the quality of the streaming video upon each handoff between access points. We have evaluated thresholds of RSSI and Loss Frame Rate (LFR) for deciding the moment when the handoff process shall begin. Our solution performance was evaluated in a testbed implementation for MPEG-4 video on demand with one video server (VLS) and two FreeBSD-based access points supporting Mobile IP, DHCP Server and IAPP approach.